Synthesis and crystal structure studies of organic salts, co-crystals and metal-organic compounds / Siti Artikah Mahmud Safbri - Siti Artikah, Mahmud Safbri (2017)
All prepared compounds were fully characterized via FT- IR spectroscopic technique and elemental analysis; CHN including melting point, PXRD and SCXRD. The first project covers the synthesis of organic salts and co-crystals using carboxylic acid; 2-amino-4-chlorobenzoic acid (BA) and 1, 2, 4, 5-benzenetetracarboxylic acid (TCA) in combination with amines: piperazine (PIP), 1-methylpiperazine (MPIP), 1, 10-phenanthroline (PHEN), and 2-dipyridylketone (DPK) respectively in 1:1 ratios via mechanochemical grinding and vapor diffusion techniques. This series successfully obtained four organic salts and four co-crystals. The reaction of BA-PIP and BA-MPIP show deprotonation of carboxylic acid and protonation of amine in the solid state. Reaction of TCA-DPK results in formation of co-crystals whilst TCA-PHEN shows the formation of organic salts. Structural studies reveal that these organic molecules undergo molecular recognition process to obtain a range of two dimensional networks through persistent hydrogen-bonding patterns adopted by certain functional groups, which acts as template and rely on the robustness of such motifs to create new solid- state structures. The second project aims to synthesis of crystals using Zn2+ and Cd2+ to form metal complexes with -S2CN(CH2CH2OH)R ligand where R = isopropyl, hydroxyethyl, methyl groups. A total of 4 metal-organic compounds were obtained which serves as a precursor in preparing mixed ligand complexes with 2, 2-bipyridyl (BIPY), PIP, PHEN and pyrazine (PYR). Results show that the presence of the N donor ligands increases the dimensionality in the crystal structure. Apart from that, PXRD pattern shows that the single crystals are the representative of the bulk materials obtained from the normal solution technique.